Aktueller Stand der Lebensqualitätsmessung bei Patienten mit chronischer Otitis media und Schallleitungsschwerhörigkeit - Lailach, Susen; Baumann, Ingo; Zahnert, Thomas; Neudert, Marcus (HNO, 2018)
The evaluation of results after middle ear reconstruction has been mainly based on functional parameters. In clinical practice as well as in otological research, the pure tone audiogram represents the gold standard in the assessment of the postoperative outcome. In order to assess the patient’s subjective outcome, outcome analyzes focus increasingly on the health-related quality of life (HRQOL). However, the evaluation of HRQOL requires reliable and validated measuring instruments. A modest number of validated questionnaires for determination of the disease-specific HRQOL in patients with chronic otitis media and/or conductive hearing loss are currently available. Three of seven available questionnaires were developed and validated in the German-speaking countries, the Zurich Chronic Middle Ear Inventory 21 (ZCMEI-21), the Chronic Otitis Media Outcome Test 15 (COMOT-15) and the Stapesplasty Outcome Test 25 (SPOT-25). In this review, all seven available disease-specific measuring instruments as well as the generic questionnaires, which were used in previous clinical trials, are explained and current findings of quality-of-life research in patients with chronic otitis media and/or conductive hearing loss are presented.